On the Formation of Lava Flows and Lava Domes in Mafic-Intermediate Magmas (Mount Ungaran, Central Java, Indonesia) - Suhendro, Indranova; Al Aro, Adrianto Shifa; Palembang, Muhammad Fikram; Rahim, Ariqonitahanif Putri; Sari, Lusi Ratna (Pleiades Publishing, 2023)
Abstract: In this study, we combined the results of petrography pheno-crystallinity (φPC) and magma compositions (bulk and melt compositions) to calculate the magma viscosity (μeff) of the lava flows and domes that erupted from Mount Ungaran, Central Java, Indonesia. The lava flows were characterized by slightly larger SiO2 variations than those of lava domes, with a large overlap between each phase (46.7–57.8 and 53.2–59.8 wt % SiO2, respectively). However, lava flows were typically less crystalline than the lava domes (average φPC of 33 and 40%, respectively). Because lava flows share an identical composition to lava domes and temperature is inversely proportional to SiO2 content, it is inferred that magma composition and temperature did not play a substantial role in controlling magma viscosity. Instead, we found that pheno-crystallinity was the most important parameter. Specially, for a ±7% difference of pheno-crystallinity (at a given SiO2), magma viscosity could differ by one order of magnitude, ultimately controlling lava morphology: high-viscosity magma (5.6–7.8 log Pa s) formed lava domes, whereas low-viscosity magma (4.6–6.6 log Pa s) produced lava flow. Moreover, we found that lava dome samples exhibited gentler phenocryst size distribution (CSD) slopes than lava flow samples (2.1–3.4 and 2.7–6.9, respectively). Because the CSD slope was inversely proportional to the magma residence time (CSD slope = –1/Gt), we suggest that lava dome formation, which requires a high magma viscosity, originates from a longer-lived and more crystalline magma, whereas lava flow with low magma viscosity originates from a young and less crystalline magma. Thus, in the case of mafic-to-intermediate magma, as in the present case, we think that the resultant lava morphology is strongly controlled by the abundance of phenocrysts and magma residence time. © 2023, Pleiades Publishing, Ltd.